The creation of the Inuit siku (sea ice) atlas - Ljubicic, G. (Gita); Pulsifer, P. (Peter); Hayes, A. (Amos); Taylor, D.R. (Fraser) (2014)
The sea ice continues to be an important part of life in Inuit communities, and local Elders and hunters wanted to have their detailed knowledge of the sea ice documented to help share with Inuit youth. Developing the Inuit siku (sea ice) Atlas was seen as one important way of sharing this local expertise more broadly, with youth in schools across Nunavut, with scientists interested in the northern marine environment, and with the general public. Through long-term working relationships, and funding from the International Polar Year Inuit Sea Ice Use and Occupancy Project, Elders and hunters in Cape Dorset, Igloolik, and Pangnirtung, Nunavut, worked with researchers to develop the siku Atlas to reflect their knowledge and uses of the sea ice. In this chapter, we provide some background on the evolution of the project and rationale for the Atlas development. We then highlight the key components of the siku Atlas, as well as technical innovations that emerged through efforts to address community interests. Finally, we share some lessons learned in the process of Atlas creation, including the necessary emphasis on relationality, the need for ongoing community consultations and verification, the incredible time commitments involved, the amount of time dedicated to Atlas conceptualization, the importance of having accessible technical expertise, and efforts to ensure that the Atlas becomes a living resource.